Politicized enforcement in Argentina : labor and environmental regulation - Amengual, Matthew (Cambridge : Cambridge University Press, 2016)
Countries throughout the world have passed regulations that promise protection for workers and the environment, but violations of these policies are more common than compliance. All too often, limitations of state capacity and political will intertwine hindering enforcement. Why do states enforce regulations in some places, and in some industries, but not in others? In Politicized Enforcement in Argentina, Amengual develops a framework for analyzing enforcement in middle-income and developing countries, showing how informal linkages between state officials and groups within society allow officials to gain the operational resources and political support necessary for enforcement. This analysis builds on state-society approaches in comparative politics, but in contrast to theories that emphasize state autonomy, it focuses on key differences in the way states are porous to political influence.
Machine generated contents note: 1. Introduction. the challenge of enforcement; 2. Explaining enforcement of labor and environmental regulations; Part I. Labor Regulation: 3. Labor regulation in Argentina; 4. Enforcement with unions in the driver's seat; 5. State-driven and co-produced enforcement in labor regulation; Part II. Environmental Regulation: 6. Chaotic environmental regulation in Argentina; 7. Putting out fires in Santa Fe and Cordoba; 8. Pollution in the'Garden of the Republic'; 9. Conclusion; Appendix. List of interviews in Argentina.
Title from publisher's bibliographic system (viewed on 07 Jan 2016).
Keywords: Administrative agencies -- Argentina; Environmental agencies -- Argentina; Labor laws and legislation -- Argentina; Labor policy -- Argentina; Environmental law -- Argentina; Environmental policy -- Argentina -- Citizen participation; Industrial laws and legislation -- Argentina; Industrial policy -- Argentina